Identification of rare sequence variation underlying heritable pulmonary arterial hypertension - Gräf, Stefan; Haimel, Matthias; Bleda, Marta; Hadinnapola, Charaka; Southgate, Laura; Li, Wei; Hodgson, Joshua; Liu, Bin; Salmon, Richard M.; Southwood, Mark; Machado, Rajiv D.; Martin, Jennifer M.; et al. (Nature communications, 2018)
Pulmonary arterial hypertension (PAH) is a rare disorder with a poor prognosis. Deleterious variation within components of the transforming growth factor-β pathway, particularly the bone morphogenetic protein type 2 receptor ( BMPR2 ), underlies most heritable forms of PAH. To identify the missing heritability we perform whole-genome sequencing in 1038 PAH index cases and 6385 PAH-negative control subjects. Case-control analyses reveal significant overrepresentation of rare variants in ATP13A3, AQP1 and SOX17 , and provide independent validation of a critical role for GDF2 in PAH. We demonstrate familial segregation of mutations in SOX17 and AQP1 with PAH. Mutations in GDF2 , encoding a BMPR2 ligand, lead to reduced secretion from transfected cells. In addition, we identify pathogenic mutations in the majority of previously reported PAH genes, and provide evidence for further putative genes. Taken together these findings contribute new insights into the molecular basis of PAH and indicate unexplored pathways for therapeutic intervention. Pulmonary arterial hypertension (PAH) is a rare lung disorder characterised by narrowing and obliteration of small pulmonary arteries ultimately leading to right heart failure. Here, the authors sequence whole genomes of over 1000 PAH patients and identify likely causal variants in GDF2 , ATP13A3 , AQP1 and SOX17 .